Development of a hot water disinfestation treatment for taro exported from the Pacific Islands - Jamieson, L.E.; Chhagan, A.; Redpath, S.P.; Griffin, M.J.; Rohan, C.; Tunupopo, F.; Tugaga, A.; Connolly, P.G.; Woolf, A.B. (New Zealand Plant Protection, 2016)
Taro imported to New Zealand from the Pacific Islands are currently fumigated with methyl bromide (MB) for control of mites nematodes and other quarantine pests There are growing restrictions on the use of MB and alternatives to this fumigant are being sought such as hot water treatments Mites (Rhizoglyphus minutus) and nematodes (Meloidogyne sp or Helicotylenchus sp) were exposed to hot water both on and off taro Hot water exposures ranged from 475C to 525C for 15 s to 5 min the duration depending on the temperature Preliminary off taro experiments indicated that 100 mortality of R minutus mite adults was achieved in 34 min at 475C and between 30 s and 1 min at 50C All adult mites were dead at the shortest treatment duration (15 s) at 525C The results indicated that 100 mortality of juvenile Meloidogyne sp was achieved in 12 min at 475C and between 30 s and 1 min at 50C All juvenile nematodes were dead at 45 s at 525C Preliminary on taro experiments at 525C for durations of 35 min and 5 min indicated that a longer duration would be required to achieve 100 mortality of Rhizoglyphus mites No live Meloidogyne or Helicotylenchus nematodes were present in either the untreated or hot watertreated taro